2020
DOI: 10.1186/s42077-020-00091-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative randomized study of continuous serratus anterior plane block versus continuous paravertebral block in post-mastectomy pain

Abstract: Background Many analgesic methods have been used to control post-mastectomy pain. Both thoracic paravertebral and serratus anterior blocks are recent regional techniques with promising results. The aim of this study was to compare safety and analgesic efficacy of both techniques in controlling post-mastectomy pain. Methods The study was conducted from January 1, 2019, till January 10, 2019, on 60 female patients ASA class ≤ 2 undergoing modified radical mastectomy. After induction of balanced general anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In addition, pectoralis major muscle is supplied by pectoral nerves which are branches from brachial plexus not thoracic nerves explaining the pain with abduction of the arm. [16,19] There was significant tachycardia in the SAPB group in the intraoperative, immediately postoperative and 2 hours postoperative with p value 0.001, 0.004 and 0.001 respectively.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, pectoralis major muscle is supplied by pectoral nerves which are branches from brachial plexus not thoracic nerves explaining the pain with abduction of the arm. [16,19] There was significant tachycardia in the SAPB group in the intraoperative, immediately postoperative and 2 hours postoperative with p value 0.001, 0.004 and 0.001 respectively.…”
Section: Resultsmentioning
confidence: 89%
“…VAS scores postoperatively were comparable in the two groups, also postoperative morphine consumption in the 24 hrs was significantly higher in the SAPB group vs the TPVB group [9.7 ± 2.1 mg vs 6.5 ± 1.5, P < 0.001,]. Mahran et al, [16] compared ultrasound guided continuous SAPB and continuous TPVB for pain relief following MRM with axillary dissection. They found that the time for the first analgesic drug request was significantly increased in TPVB 368 ± 36.0 min vs 270.2 ± 37.7 for SAPB p < 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…We finally excluded 5 studies and identified 16 RCTs in this systematic review and meta-analysis. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] One study 20 did not report data amenable for a pooled analysis and hence was not included.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The included studies are shown in Table 1. Thirteen studies [19][20][21][22][23][24]27,[29][30][31][32][33][34] compared SAB versus PVB, whereas only 3 studies 25,26,28 compared SAB with ICB. Of the total 16 studies, 5 each were conducted in India and Egypt.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation